2011
DOI: 10.1038/ncomms1522
|View full text |Cite
|
Sign up to set email alerts
|

Malaria parasite tyrosyl-tRNA synthetase secretion triggers pro-inflammatory responses

Abstract: malaria infection triggers pro-inflammatory responses in humans that are detrimental to host health. Parasite-induced enhancement in cytokine levels correlate with malariaassociated pathologies. Here we show that parasite tyrosyl-tRnA synthetase (PfTyrRs), a housekeeping protein translation enzyme, induces pro-inflammatory responses from host immune cells. PfTyrRs exits from the parasite cytoplasm into the infected red blood cell (iRBC) cytoplasm, from where it is released into the extracellular medium on iRBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 54 publications
(130 reference statements)
0
72
0
Order By: Relevance
“…Plasmodium falciparum possesses 36 aaRSs, which show asymmetric distributions among parasite organelles (7,8,13,14). The presence of appended domains imparts characteristic functions to parasite aaRSs (13)(14)(15). For example, recent studies have revealed cytokine-like functions for malaria tyrosyl-tRNA synthetase (tyrosyl-RS) (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmodium falciparum possesses 36 aaRSs, which show asymmetric distributions among parasite organelles (7,8,13,14). The presence of appended domains imparts characteristic functions to parasite aaRSs (13)(14)(15). For example, recent studies have revealed cytokine-like functions for malaria tyrosyl-tRNA synthetase (tyrosyl-RS) (15).…”
mentioning
confidence: 99%
“…The presence of appended domains imparts characteristic functions to parasite aaRSs (13)(14)(15). For example, recent studies have revealed cytokine-like functions for malaria tyrosyl-tRNA synthetase (tyrosyl-RS) (15).…”
mentioning
confidence: 99%
“…Although hemozoin itself does not induce endothelial barrier dysfunction, 47,49 it has been shown to activate NF-kB signaling pathways as shown by increased IL-8 and MCP-1 (CCL2) production in HUVEC. 118 Other parasite derived products such as DNA, 119,120 histones, 121 tRNA synthetase, 120 uric acid 122 and heat shock proteins (HSP) 123 have been shown to activate the host immune system. In the case of histones, they can disrupt endothelia into renal arteries l barrier function.…”
mentioning
confidence: 99%
“…The few parasite-specific studies available on TyrRS have majorly focused on the structural aspects of the enzyme. A recent comprehensive study highlighted the structural and functional aspect of TyrRS from Plasmodium falciparum (24). The structural analysis of the TyrRS orthologue from L. major reveals several crucial differences between the host and pathogen tyrosyl-tRNA synthetase active sites (13).…”
Section: Discussionmentioning
confidence: 99%
“…immune cells (23)(24)(25). Direct binding of rLdTyrRS to host macrophages was visualized by immunofluorescence analysis.…”
Section: A-c)mentioning
confidence: 99%